Meta-analysis of Indonesian Octopus laqueus Kaneko & Kubodera 2005 (Cephalopoda: Octopodidae) using Mt-DNA COI as Genetic Marker - Nenik Kholilah; Norma Afiati; Subagiyo Subagiyo; Retno Hartati (Jurnal Kelautan Tropis, 2021)
O. laqueus was first discovered not long ago in 2005 in the Ryuku Islands, Japan. Its geographical distribution and molecular identification are therefore still rarely. Nucleotide sequences based on mt-DNA COI for O. laqueus that have been uploaded in the GenBank until before this study was carried out were only six sequences. Since DNA barcoding of mt-DNA COI has some advantageous characteristics, this study aimed to analyse the genetic difference of Indonesian O. laqueus to the data available in the GenBank. Samples were collected in 2019 - 2020 from Karimunjawa (n=16) and Bangka-Belitung (n=2). The mt-DNA COI was extracted using 10% chelex methods, PCR amplified using Folmer’s primer and sequenced in Sanger methods. Pairwise alignment and genetic distance were carried out in MEGA-X, whereas the phylogenetic tree was reconstructed using Bayesian methods. BLAST identification resulted in 685 bp with a range of 92,07-99,24  percentages of identity. The genetic mean pair-wise distances within-clade were 0,002 and 0,006, whilst the distance between the clade was 0.0883. Combining the suggestion with the ITF current, it is concluded that O. laqueus taken from Karimunjawa raised from the same species as those in Malaysia (MN711655) and Japan (AB302176). Specimens from Bangka-Belitung were suggested came from different species, as they were separated into the second clade by 8.83%. One single sample from Japan (AB430543) which laid outside the two clades by 11.63%-11.38% was also suggested to represent a different species. Overall, this study opens to various further studies on O. laqueus using other loci of genetic markers.